Just Traveling : God, Leaving Home, and a Spirituality for the Road - Hamman, Jaco J. (Book collections on Project MUSE., 2021)
Just Traveling celebrates moving at the speed of being present to one's experiences, bridging distance and difference through acts of care. Following the scriptural witness of God as the Earthroamer, the book explores the liminal qualities of traveling through six movements: anticipating, leaving, surrendering, meeting, caring, and returning. Whether leaving home serves our wanderlust and curiosity or has personal or spiritual purposes, when we travel, we explore a beautiful, yet complex and troubled world.